Building Sustainable Entrepreneurship with a Science-Based Green Entrepreneurship Learning Model and Sustainable Development Goals in Islamic Boarding Schools - Meishanti, Ospa Pea Yuanita; Susantini, Endang; Puspitawati, Rinie Pratiwi; Sari, Kartika; Putri, Rossanita Truelovin Hadi (Universitas Negeri Semarang, 2025)
The purpose of this research is to examine the implementation process of the Green Entrepreneurship project model to build sustainable entrepreneurship grounded in science and the SDGs in Islamic boarding schools. The qualitative approach of the grounded theory method: 1) Determining the design; 2) Formulating the problem; 3) Access to the research setting; 4) Data collection procedures; 5) Coding process; 6) Selective coding; 7. Validation of the theory. Data collection techniques: interviews, observations, and documentation of informants. Data analysis techniques from the researcher's entry into the field through the end of the research: displaying, reducing, analyzing, and concluding data. Data validity test: triangulation of credibility tests, member checks, and audit trails with VOSviewer novelty analysis. The results of the study show a three-dimensional transformation of Islamic boarding school entrepreneurship, namely Islamic spirituality as the foundation of values ​​of concern for God's creation based on environmentally friendly businesses, integration of science not only spiritual values, but using scientific methods, technology, and innovative, efficient, sustainable business research, and innovation technology, as well as ecological awareness as a sustainable direction so that the theory is formed